Effect of lace-up ankle brace on the tibiotalar and subtalar joint during the landing - Luo, Ye; Hu, Mengling; Li, Zhuman; Huang, Xiaofan; Wu, Danni; Li, Feng; Wang, Shaobai (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Ankle braces can affect the kinematics of the ankle joint during landing tasks. Previous studies were primarily relied on traditional marker-based motion capture systems, which pose limitations in non-invasively capturing the motion of the talus bone. The effect of ankle braces on the in vivo kinematics of the tibiotalar and subtalar joints during landing remains unknown. This study used a high-speed dual fluoroscopic imaging system (DFIS) and magnetic resonance imaging (MRI) to investigate effect of ankle braces on the in vivo kinematics of the tibiotalar and subtalar joints during landing.Methods: Fourteen healthy participants were recruited for this study. During the experiment, static three-dimensional MRI data were collected for each participant, and 3D ankle joint models for the calcaneus, talus, and tibia were constructed. The DFIS was used to capture the images of each participant performing a single-leg landing-jump task at a height of 40 cm. The images were captured once with and without a brace in the fatigue condition, which was induced by running. The sixdegree-of-freedom (6DOF) kinematic data were obtained by 2D-3D registration.The flexion-extension range of motion (ROM) (42.73±4.76° vs 38.74±5.43°, p=0.049) and anterior-posterior translation ROM (16.86±1.74 mm vs 15.03±1.73 mm, p=0.009) of the tibiotalar joint were decreased. The maximum inversion angle (-3.71±2.25° vs 2.11±1.83°, p=0.047) of the subtalar joint was decreased.The ankle brace limited the flexion-extension ROM of the tibiotalar joints and the inversion angle of the subtalar joint during landing.